2018
DOI: 10.1063/1.5025724
|View full text |Cite
|
Sign up to set email alerts
|

Development and modeling of a polar-direct-drive exploding pusher platform at the National Ignition Facility

Abstract: High-intensity laser facilities, such as the National Ignition Facility (NIF), enable the experimental investigation of plasmas under extreme, high-energy-density conditions. Motivated by validating models for collisional heat-transfer processes in high-energy-density plasmas, we have developed an exploding pusher platform for use at the NIF in the polar-direct-drive configuration. The baseline design employs a 3 mm-diameter capsule, an 18 μm-thick CH ablator, and Ar-doped D2 gas to achieve several keV electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Also, their cases involved a converging geometry and pressures and temperatures orders of magnitude larger than those in the present study. Hence, the impact of neglecting barodiffusion and thermodiffusion is expected to be less in the present study than in Ellison et al (2018). We stress that the assessment of simplified models of mass diffusion in HED flows remains an active area of research.…”
Section: A4 Properties Of Multispecies Mixturesmentioning
confidence: 76%
See 3 more Smart Citations
“…Also, their cases involved a converging geometry and pressures and temperatures orders of magnitude larger than those in the present study. Hence, the impact of neglecting barodiffusion and thermodiffusion is expected to be less in the present study than in Ellison et al (2018). We stress that the assessment of simplified models of mass diffusion in HED flows remains an active area of research.…”
Section: A4 Properties Of Multispecies Mixturesmentioning
confidence: 76%
“…It is a considerable simplification of the physics of multispecies diffusion, and it is expected to be most accurate for mixtures of ions with similar masses and charges. Ellison et al (2018) found that it gave reasonable order-of-magnitude results for an ICF-relevant flow. Specifically, they reported that diffusive mixing between various combinations of five atomic species was larger, in a majority of cases, when using the OCP approximation instead of higher-fidelity approaches.…”
Section: A4 Properties Of Multispecies Mixturesmentioning
confidence: 86%
See 2 more Smart Citations
“…Relatively large (3-mm diameter) think capsules are being developed for PDD exploding pusher studies with the aim of creating high ion temperature (>10 keV) conditions for plasma physics studies and as neutron sources. NIF experiments using plastic capsules were well-modeled by one-dimensional simulations [113]. Higher gas-fill pressures at room temperature will increase the yield of the platform and increase the design space for optimization.…”
Section: Direct-drive Platformsmentioning
confidence: 99%